2020
DOI: 10.1093/ehjci/jeaa009
|View full text |Cite|
|
Sign up to set email alerts
|

The evaluation of aortic stenosis, how the new guidelines are implemented across Europe: a survey by EACVI

Abstract: Aortic stenosis (AS) is the most prevalent valvular disease in developed countries, with a prevalence that is set to expand further with an ageing population. The most recent guidelines on valvular heart disease published by the European Society of Cardiology and the European Association for Cardio-Thoracic Surgery, aim to standardize the diagnosis and management of valvular heart diseases. The imaging criteria of the current guidelines are mostly based on EACVI Recommendations, with an appropriate diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…A recent survey evidenced that only half of the centers reported the routine calculation of the SVi in these patients in Europe, indicating limited adherence to ESC guidelines. [50] Despite these perplexities, no prospective randomized trial has still conducted to evaluate the optimal management of patients with LG-AS. Of note, there are also some contemporary data suggesting that moderate AS (i.e., pseudo-severe AS) may not be a benign stage in the evolution of the disease as the conventional wisdom tells us almost in patients at an advanced stage of cardiac damage and high risk of rapid progression of AS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey evidenced that only half of the centers reported the routine calculation of the SVi in these patients in Europe, indicating limited adherence to ESC guidelines. [50] Despite these perplexities, no prospective randomized trial has still conducted to evaluate the optimal management of patients with LG-AS. Of note, there are also some contemporary data suggesting that moderate AS (i.e., pseudo-severe AS) may not be a benign stage in the evolution of the disease as the conventional wisdom tells us almost in patients at an advanced stage of cardiac damage and high risk of rapid progression of AS.…”
Section: Discussionmentioning
confidence: 99%
“…Recently TAVI is also recommended for patients with intermediate surgical risk. Currently, publish literature also supports TAVI implantation in low risk patients as non-inferior to surgical therapy [55,56].…”
Section: Management Of Aortic Valve Stenosismentioning
confidence: 97%
“…The importance of a careful and comprehensive multi-window acquisition cannot be emphasized enough, since in up to 50% of patients with AS the peak velocity is obtained in a right parasternal view (37,39,40). However, a recent EACVI survey including 125 centers from 32 countries (87% of them tertiary/university high-volume centers) showed that almost half of them did not routinely obtained measurements from the right parasternal view (41). Therefore, before moving to advanced non-invasive imaging, it is fundamental to ensure an optimal echocardiographic acquisition ( Figure 3).…”
Section: Validation Of Rest Echocardiographic Parametersmentioning
confidence: 99%